Assessment criteria for lack of stability in the hip joint in cases of acetabular fractures - Kanziuba, Anatoly; Shamova, Tatyana (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
The purpose of the present research was to determine criteria and possible methods of diagnosis of hip joint instability in different variants of acetabular fractures. Assessment of stability of a damaged hip joint should be based on the revealing of clinical and radiological criteria. Destruction of the roof, posterior and medial walls of the acetabulum by results of its radiographic and KT studies are the most important criteria.